Urban Solutions in the Universal Planning of Residential Spaces for the Elderly and the Disabled - Wojtyszyn, Bogusław J. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concerns the creation, in accordance with the EU idea of integrated accessibility, more and more favorable legal and design conditions for shaping the space of the residential development environment with equalized physical and social accessibility among elderly, disabled and non-disabled people. The research results presented in the article indicate the existing limitations and new possibilities in improving the general principles of creating urban assumptions for universal design.
Keywords: residential buildings; construction for the disabled; accessibility of residential development space; environment of the elderly; urban planning; budynki mieszkalne; budownictwo dla niepełnosprawnych; środowisko osób starszych; mieszkalnictwo